Book Review of "Insider Threats" by Matthew Bunn and Scott D. Sagan - Arjun Banerjee (International Journal of Nuclear Security, 2019)
While books on various kinds of insider threats do exist, meticulously compiled information on the topic in the context of nuclear security is hard to come by. Information in the nuclear domain rarely comes to light for security reasons and makes this strain of insider threats a challenging topic to write about. This edited volume entitled Insider Threats, compiled by two of the most respected Professors in the field of nuclear security today, namely Matthew Bunn of Harvard University, and Scott D. Sagan of Stanford University, arrived on bookshelves as a timely publication.